2021
DOI: 10.1111/mms.12860
|View full text |Cite
|
Sign up to set email alerts
|

Passive acoustic monitoring reveals feeding attempts at close range from soaking demersal longlines by two killer whale ecotypes

Abstract: Odontocetes depredating fish caught on longlines is a serious socio-economic and conservation issue. A good understanding of the underwater depredation behavior by odontocetes is therefore required. Historically, depredation on demersal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 86 publications
(189 reference statements)
0
11
0
Order By: Relevance
“…This acoustic approach could then be complementary to traditional visual counting from the vessel at hauling (Roche et al 2007; Tixier et al 2010). However, the acoustic method has the added advantage that whales can be counted also when the fishing vessels are not hauling, and thus have no visual observers in action (Richard et al 2022). Also, in some of the deployments reported here, the acoustic method counted more whales than reported by the visual observers, indicating that the latter may underestimate the real hauling interaction rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This acoustic approach could then be complementary to traditional visual counting from the vessel at hauling (Roche et al 2007; Tixier et al 2010). However, the acoustic method has the added advantage that whales can be counted also when the fishing vessels are not hauling, and thus have no visual observers in action (Richard et al 2022). Also, in some of the deployments reported here, the acoustic method counted more whales than reported by the visual observers, indicating that the latter may underestimate the real hauling interaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, (Richard et al 2020) observed plausible evidence of sperm whale depredation on demersal soaking longlines using accelerometers fixed on longlines' hooks, with an event confirmed by the entanglement of a sperm whale. Indeed, settings have specific acoustic signature which could attract attention of odontocetes before soaking (Richard et al 2022). Nevertheless, this study was based on a limited dataset and the occurrence of depredation behaviour on soaking longlines could not be quantified.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations